PENGARUH NILAI-NILAI MULTIKULTURAL TERHADAP MENUMBUHKEMBANGKAN KARAKTER NASIONALIS - Rahmat Rahmat; Lu’lu’ il Maknuun (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2020)
Every individual is required to have good character in their daily lives. Whereas character education is the responsibility of each individual too, which in this context, can be started from the surrounding environment both at home and in the school education environment. Thus, it is necessary to identify related factors that greatly affect the improvement of character, especially the character of nationalism. This article tries to explain the influence of multicultural values on developing nationalist characters for students. Therefore, the selection of appropriate multicultural values will greatly influence the growth of nationalist character for students. With quantitative methods, utilizing survey techniques in the form of questionnaires. Then, the questionnaire was submitted to the students of class XII International Standard Madrasah Aliyah (MBI) Amanatul Ummah Mojokerto to then be able to find out the influence of multicultural values on the development of nationalist character.